Pengaruh Kepemimpinan Transformasional Dan Work Life Balance Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening - Muslih, Muslih; Hasibuan, Saripuddin; Handayanai, Cici (Maneggio: Jurnal Ilmiah Magister Manajemen, 2025)
The purpose of this study was to determine the effect of transformational leadership and work-life balance on employee performance through job satisfaction as an intervening variable at PTPN IV Regional II PKS Dolok Ilir. Both directly and indirectly. This study uses a quantitative approach and statistical analysis, namely the partial least square - structural equation model (PLSSEM) which aims to conduct path analysis with latent variables. The results of the study indicate that transformational leadership has a significant effect on employee performance at PTPN IV Regional II PKS Dolok Ilir. Work-life balance has a significant effect on employee performance at PTPN IV Regional II PKS Dolok Ilir. Transformational leadership has a significant effect on job satisfaction at PTPN IV Regional II PKS Dolok Ilir. Work-life balance has a significant effect on job satisfaction at PTPN IV Regional II PKS Dolok Ilir. Job satisfaction has a significant effect on employee performance at PTPN IV Regional II PKS Dolok Ilir. Transformational leadership has a significant effect on employee performance through job satisfaction at PTPN IV Regional II PKS Dolok Ilir. Work-life balance has a significant effect on employee performance through job satisfaction at PTPN IV Regional II PKS Dolok Ilir.